On the Road to Sustainable Urban and Transport Development in the Automobile Society? Traced Narratives of Car-Reduced Neighborhoods - Selzer, Sina; Lanzendorf, Martin (Sustainability, 2019)
Worldwide, academics and practitioners are developing ‘planning-oriented’ approaches to reduce the negative impacts of car traffic for more sustainable urban and transport development. One such example is the design of car-reduced neighborhoods, although these are controversial issues in the hegemonic ‘system’ of automobility. Despite the reduction of emissions and frequent recognition as ‘best practice examples’, ‘planning-critical’ research questions the underlying objectives and narratives of such sustainable developments. Our study contributes to this research perspective by improving the understanding of narratives that emerge along with car-reduced housing developments. For this purpose, we analyze two car-reduced neighborhoods in the City of Darmstadt (Germany) by conducting interviews with different actors involved in the planning and implementation processes. Our investigation reveals that the development of car-reduced neighborhoods (i) is consciously embedded in the context of sustainability, (ii) is characterized by power relations, (iii) follows normative indicators, and (iv) does not always correspond to lived realities. Altogether, the traced narratives of car-reduced neighborhoods are embedded in the overarching debate on sustainability, while at the same time revealing the dependence of society on the automobile. Thus, the hegemonic ‘system’ of automobility—although it is beginning to crack—continues to exist.